2022
DOI: 10.1021/acs.jpclett.2c02313
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Nuclear Magnetic Resonance of Triple-Cation Mixed-Halide Perovskites

Abstract: Mixed-cation lead mixed-halide perovskites are the best candidates for perovskite-based photovoltaics, thanks to their higher efficiency and stability compared to the single-cation single-halide parent compounds. TripleMix (Cs 0.05 MA 0.14 FA 0.81 PbI 2.55 Br 0.45 with FA = formamidinium and MA = methylammonium) is one of the most efficient and stable mixed perovskites for single-junction solar cells. The microscopic reasons why triplecation perovskites perform so well are still under debate. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The FA-rich cation alloys such as Cs 0.05 (MA 0.17 FA 0.83 ) 0.95 Pb­(Br 0.17 I 0.83 ) 3 (CsMAFA) have been used to develop high-performing single-junction PSCs with PCE over 23% as well as tandem devices with silicon with a certified PCE of over 29% . The introduction of Cs + and FA + cations is expected to enhance the thermal stability of the perovskite material. , Although the instability in FAPbI 3 is studied by multiscale characterization techniques, the moisture-induced degradation reactions in triple-cation CsMAFA are seldom studied. , Changes in the local structures of A site cations such as Cs + , MA + , and FA + in this formulation can be investigated by ssNMR spectroscopy. Specifically, the high sensitivity due to 100% isotopic natural abundance and moderate gyromagnetic ratio, γ­( 133 Cs) = 0.13 γ­( 1 H) and spin I = 7/2, and sufficiently large chemical shift range associated with 133 Cs NMR enable the local chemical environments of Cs cations in perovskites to be identified and distinguished.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FA-rich cation alloys such as Cs 0.05 (MA 0.17 FA 0.83 ) 0.95 Pb­(Br 0.17 I 0.83 ) 3 (CsMAFA) have been used to develop high-performing single-junction PSCs with PCE over 23% as well as tandem devices with silicon with a certified PCE of over 29% . The introduction of Cs + and FA + cations is expected to enhance the thermal stability of the perovskite material. , Although the instability in FAPbI 3 is studied by multiscale characterization techniques, the moisture-induced degradation reactions in triple-cation CsMAFA are seldom studied. , Changes in the local structures of A site cations such as Cs + , MA + , and FA + in this formulation can be investigated by ssNMR spectroscopy. Specifically, the high sensitivity due to 100% isotopic natural abundance and moderate gyromagnetic ratio, γ­( 133 Cs) = 0.13 γ­( 1 H) and spin I = 7/2, and sufficiently large chemical shift range associated with 133 Cs NMR enable the local chemical environments of Cs cations in perovskites to be identified and distinguished.…”
Section: Resultsmentioning
confidence: 99%
“…82,83 Although the instability in FAPbI 3 is studied by multiscale characterization techniques, the moisture-induced degradation reactions in triple-cation CsMAFA are seldom studied. 57,84 Changes in the local structures of A site cations such as Cs + , MA + , and FA + in this formulation can be investigated by ssNMR spectroscopy. Specifically, the high sensitivity due to 100% isotopic natural abundance and moderate gyromagnetic ratio, γ( 133 Cs) = 0.13 γ( 1 H) and spin I = 7/2, and sufficiently large chemical shift range associated with 133 Cs NMR enable the local chemical environments of Cs cations in perovskites to be identified and distinguished.…”
Section: Impact Of Water Vapor On Morphology and Localmentioning
confidence: 99%
“…As observed in Figure 6, nominal precursor ratios in the solution process result in films with virtually equal organic composition (or ratio). 36,44 This linear relation varies for compositions containing triple cations when the incorporation of Cs is >5%. 6 However, for vacuum-based processes, the estimation deviates from the 1:1 line when the nominal FA + content is >55% for coevaporation due to more difficult incorporation and sticking of MAI, for FA + < 50% the stoichiometry is maintained.…”
Section: Iiiiii Structural and Optical Characterization Of Mcs Ma 1−x Famentioning
confidence: 99%
“…Using this approach, the authors demonstrated the acquisition of fast MAS 207 Pb NMR spectra of intact MAPbI 3 films and that such analysis could be transferred to more complex MHP compositions to elucidate and quantify the distinct lead coordination environments. In addition, the advent of solid-state mechanochemical synthesis for MHPs has helped the adoption of ssNMR to analyze these materials as well. ,, Mechanochemical synthesis has proven to be a highly effective method for providing large quantities of high-purity and crystalline MHP materials of the desired composition without solvent interference, allowing for highly sensitive ssNMR studies including MAPbI 3 , FAPbI 3 , MA 1– x FA x PbI 3 , Cs 1– x FA x PbI 3 , (RbCsFAMA)­Pb­(I y Br 1– y ) 3 , CsFAMAPb­(I y Br 1– y ) 3 , and MAPbI y Br 1– y . Overall, NMR spectroscopy stands out as a versatile method for quantitative characterization of MHPs and the entire system they are a part of, including solvents, additives, phase composition, etc., resulting from the synthesis procedure. , Besides structural information, solid-state NMR techniques offer valuable insights into the local dynamics and the interactions that impact those dynamics. As such, it can relate properties at the atomic level to the final properties of the thin film or even the optoelectronic device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation